2020
DOI: 10.1371/journal.pone.0238511
|View full text |Cite
|
Sign up to set email alerts
|

Provider anticipation and experience of patient reaction when deprescribing guideline discordant inhaled corticosteroids

Abstract: Introduction Despite evidence of possible patient harm and substantial costs, medication overuse is persistent. Patient reaction is one potential barrier to deprescribing, but little research has assessed this in specific instances of medication discontinuation. We sought to understand Veteran and provider experience when de-implementing guideline-discordant use of inhaled corticosteroids (ICS) in those with mild-to-moderate chronic obstructive pulmonary disease (COPD). Methods We conducted a mixed-methods ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Many barriers for withdrawing medication have been shown in previous RCTs [45,46]. A study from the US on attitudes towards withdrawal of ICS in patients with COPD showed that, even though physicians worried about resistance from the patients, most patients were willing to try ICS withdrawal [47]. The patients trusted and relied on their physician's expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Many barriers for withdrawing medication have been shown in previous RCTs [45,46]. A study from the US on attitudes towards withdrawal of ICS in patients with COPD showed that, even though physicians worried about resistance from the patients, most patients were willing to try ICS withdrawal [47]. The patients trusted and relied on their physician's expertise.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent Global Initiative for Chronic Obstructive Lung Disease (GOLD) report (2023) recommends that ICS should only be administered in COPD patients who have a high risk of frequent exacerbations and on the basis of consideration of blood eosinophil indicators ( GOLD, 2023 ). However, evidence from real-world studies shows that the phenomenon of ICS overuse is pervasive, sometimes with triple therapy (its conjunction with LABA and LAMA) having been used as a common maintenance treatment for COPD patients ( Lucas et al, 2008 ; Parikh et al, 2020 ). To date, whether the long-term use of ICS triple therapy brings enough benefit to COPD patients, and the relevant mechanisms of its action, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent Global Initiative for Chronic Obstructive Lung Disease (GOLD) report (2023) recommends that ICS should only be administered in COPD patients who have a high risk of frequent exacerbations and on the basis of consideration of blood eosinophil indicators (GOLD, 2023). However, evidence from real-world studies shows that the phenomenon of ICS overuse is pervasive, sometimes with triple therapy (its conjunction with LABA and LAMA) having been used as a common maintenance treatment for COPD patients (Lucas et al, 2008;Parikh et al, 2020). To date, whether the long-term use of ICS triple therapy brings enough benefit to COPD patients, and the relevant mechanisms of its action, remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%